Portable vehicle borescope device with built-in image acquisition and processing technology - Dang , Quang Vinh; Nguyen, Bá Hải (Journal of Technical Education Science, 2014)
This research paper focuses on research into and development of the portable vehicle bore scope device with built-in image acquisition and processing technology with the aim of enabling direct and inside testing of the surface of vehicle-engine parts with ease. The device is equipped with a probe to which a super-mini camera is attached in order to enable inside exploring of engine parts. Concurrently, via a monitor, this device is able to automatically detect defects and send error codes to notify users the failure status of parts. This device is operated through a program which is programmed with the image – processing software by Labview. It has been tested on over 10 different engines with early satisfactory result.